2018
DOI: 10.17665/1676-4285.20175887
|View full text |Cite
|
Sign up to set email alerts
|

Dificuldades na aplicação do checklist cirúrgico: estudo qualitativo de abordagem ecológica restaurativa

Abstract: Aim: analyze the application of the safe surgery checklist, seeking to describe the main factors that can affect its completion and follow-up, according to the perception of nursing technicians. Method: this is a qualitative study performed with nursing technicians from an outpatient surgical center in southern Brazil. The data were collected through focus groups and photographic methods, from the perspective of ecological and restorative thinking. Results: three categories emerged from the information groupin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
5
0
5
Order By: Relevance
“…We classified each of the 14 intervention-related articles according to the identified subcategories for each intervention phase (ie, before, during, and after implementation). We found that 6 (42.9%) of the 14 articles addressed at least one strategy before implementation, 17,19,21,22,30,36 13 (92.8%) of the 14 articles addressed at least one strategy during implementation, 16,17,19,21,22,25,29,30,33,34,36,38,39 and 8 (57.1%) of the 14 articles addressed at least one strategy after implementation. 17,19,[21][22][23]33,34,36 Although the remaining 14 articles did not address interventions, they provided support for the intervention strategies.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…We classified each of the 14 intervention-related articles according to the identified subcategories for each intervention phase (ie, before, during, and after implementation). We found that 6 (42.9%) of the 14 articles addressed at least one strategy before implementation, 17,19,21,22,30,36 13 (92.8%) of the 14 articles addressed at least one strategy during implementation, 16,17,19,21,22,25,29,30,33,34,36,38,39 and 8 (57.1%) of the 14 articles addressed at least one strategy after implementation. 17,19,[21][22][23]33,34,36 Although the remaining 14 articles did not address interventions, they provided support for the intervention strategies.…”
Section: Resultsmentioning
confidence: 86%
“…33 Some programs include the use of technologies during educational activities, 19,38 including explanatory videos showing how the SSC should and should not be used. 16,21,28,39 Adapting Surgical Safety Checklist training tools to meet the specific needs of an organization and its staff members rather than using the WHO standardized tools can result in higher participation.…”
Section: Providing Training Programsmentioning
confidence: 99%
“…Of the 1912 publications retrieved from the database searches, a total of 34 studies were included (Figure 1) (Page et al, 2021). The studies were conducted in a range of countries: Jordon 1 (Albsoul et al, 2022), Turkey 1 (Aydin Akbuga et al, 2023), Brazil 1 (De Oliveira Junior & De Magalhães, 2017), France 1 (Fourcade et al, 2012), Cyprus 1 (Georgiou et al, 2018), Thailand 1 (Kasatpibal et al, 2018), Sweden 3 (Krupic et al, 2020; Nordström & Wihlborg, 2019; Rönnberg & Nilsson, 2015), Saudi Arabia 1 (Manamela et al, 2022), Zambia 1 (Munthali et al, 2022), Spain 1 (Peñataro‐Pintado et al, 2021), Switzerland 1 (Schwendimann et al, 2019), New Zealand 1 (Weller et al, 2018) and Madagascar 1 (White et al, 2018), USA 2 (Alidina et al, 2017; Conley et al, 2011), multiple countries 2 (Aveling et al, 2013; Elam et al, 2022), Norway 3 (Haugen et al, 2015; Høyland et al, 2014; Wæhle et al, 2012), UK 3 (O'brien et al, 2017; Robertson‐Smith, 2016; Russ et al, 2015), Australia 4 (Braaf et al, 2013; Gillespie, Marshall, et al, 2016; Gillespie, Withers, et al, 2016; Rogers et al, 2020) and Canada 6 (Dharampal et al, 2016; Gagliardi et al, 2014; Mahmood et al, 2019; Mobilio et al, 2022; Spence et al, 2011; Ziman et al, 2018). The sample sizes ranged from 8 to 196 participants and represented the total number of all members of the perioperative MDT: surgeons, anaesthesiologists, operating room nurses, medical students, nurse anaesthetists, surgical trainees, theatre support workers, radiographers, nursing students, administrative staff, management and consumers (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance, attitudes and understanding, surgeon participation, patient anxiety and individual non‐technical skills were identified as individual barriers to the implementation of the WHO Surgical Safety Checklist. Across the studies, the main barrier to successful implementation was the behaviours and attitudes of senior medical staff, and in particularly the lead surgeon (Albsoul et al, 2022; Alidina et al, 2017; Aveling et al, 2013; Braaf et al, 2013; De Oliveira Junior & De Magalhães, 2017; Dharampal et al, 2016; Fourcade et al, 2012; Gagliardi et al, 2014; Georgiou et al, 2018; Kasatpibal et al, 2018; Manamela et al, 2022; Mobilio et al, 2022; Nordström & Wihlborg, 2019; Robertson‐Smith, 2016; Rönnberg & Nilsson, 2015; Russ et al, 2015; White et al, 2018; Ziman et al, 2018).…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation